Usefulness of Reverse Radial Forearm Flaps in Covering Soft Tissue Defects of Hand and Wrist - Sarfraz Ahmed, Maria Malik, Romaiza, Sana Riaz Hashmi, Tauqeer Nazim (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To emphasize on the importance of reverse radial forearm flap (RRF flap) in the coverage of soft tissue defects of hand and wrist. Study design: This is a descriptive experimental study. Study place and duration: Study was comprised on the period of six months from January 2022 to June 2022. It was conducted in the plastic surgery department of Allama Iqbal Memorial Teaching Hospital Sialkot Methodology: Patients with the soft tissue defects of hand and wrist due to road traffic accidents, industrial or mechanical trauma and firearm injury were admitted to the plastic surgery ward. After achieving healthy wound with wound debridement, soft tissue coverage was done using reverse radial fasciocutaneous forearm flap. Patients with amputation of thumb and those with partial or complete bone loss were excluded from the study. Ages of the patients were 17-50 years with mean age of 31.42±5.3 years. Donor site of the flap was covered with split thickness skin graft and follow-up of the patients was done for at least three months. Results: 20 cases were included in this study including 16(80%) male and 04(20%) female cases. 15(75%) cases had soft tissue defect on the dorsum of hand, 04(20%) cases had palmar defect and in 01(5%) case there was amputation at transmetacarpal level and flap coverage of the stump was done. Partial loss of the flap happened in one 01(5%) case and it was treated with debridement and skin coverage. In one case superficial epidermolysis was found and managed conservatively. Practical implication Conclusion: Reverse radial forearm fasciocutaneous flap is an excellent option for the coverage of soft tissue defects of hand and wrist due to its greater arc of rotation which makes it easy to apply to the recipient site. Key words: Hand trauma, Soft tissue defects of hand, Reverse Radial Forearm Flap, Flap Coverage of Hand